Investigating the performance of polyester microfibers in situ bags using different weft yarn count and density - Doaa Elgohary Hanafy; Dina Mohamed Hamoda; Ibrahim Mohamed Khattab; Ahmed Abdelkader Aboamer (Acta Scientiarum. Animal Sciences, 2020)
Microfiber fabrics are more efficiency in retaining fine-particles that increase the variation in in situ degradability. The aim of this was to examine the performance of in situ bags made from different microfiber fabric for meeting the required specification and their ruminal degradability compared with standard Ankom in situ bags. Four fabrics were manufactured using polyester microfiber with 1.04 denier, weft yarn counts (150 and 300), weft density (22 and 28 picks / inch), plain 1/1 textile structure. Physical and mechanical properties of manufactured fabrics were measured before and after incubation. Ruminal degradability was measured for three feedstuffs (soybean meal, wheat bran and berseem hay) using three rumen-fistulated rams as a replicates after 24 and 48 hours. Fabric's pore size was significantly decreased as either yarn weft count or density increased. Yarn weft count had a significant effect on all fabric's properties. Air permeability was significantly decreased as fabric's weft yarn count increased. Sample (1) meet the specific requirements for in situ bags and showed the nearest degradability values to those observed using Ankom bags for all feedstuffs in most incubation times. Microfiberin situ bags could be used in in situ ruminal degradation trials to reduce the variation in results due to the present of the fine particles.